2010
DOI: 10.1080/01635580903305383
|View full text |Cite
|
Sign up to set email alerts
|

Possible Benefits of Curcumin Regimen in Combination With Taxane Chemotherapy for Hormone-Refractory Prostate Cancer Treatment

Abstract: Complementary and alternative therapies for neoplastic diseases treatment and prevention receive increasing attention from the medical community. Prostate cancer (PC) is the most frequently diagnosed malignancy and the second major cause of male death in industrialized countries. The chemopreventive properties and clinical safety of curcumin, a polyphenolic derivative, have already been established. However, curcumin regimen value in addition to conventional hormone refractory (HR) PC treatment remains largely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Curcumin seems to potentiate docetaxel/prednisone with a larger action on tumor lesions. Curcumin was reported experimentally to enhance the cytotoxicity of docetaxel/prednisone through the blocking of cell cycle progression, sensitization of prostate cancer cells to apoptosis, angiogenesis inhibition and downregulation of growth factor involved in progression [35]. In our study, the CgA value was positively associated with initial PSA.…”
Section: Discussionsupporting
confidence: 58%
“…Curcumin seems to potentiate docetaxel/prednisone with a larger action on tumor lesions. Curcumin was reported experimentally to enhance the cytotoxicity of docetaxel/prednisone through the blocking of cell cycle progression, sensitization of prostate cancer cells to apoptosis, angiogenesis inhibition and downregulation of growth factor involved in progression [35]. In our study, the CgA value was positively associated with initial PSA.…”
Section: Discussionsupporting
confidence: 58%
“…Curcumin also inhibited prostate carcinogenesis (11). Studies from our laboratory and those of other authors have demonstrated enhanced anticancer activities of curcumin when combined with other anticancer agents (12)(13)(14). Findings of earlier studies showed that curcumin exerts a wide range of anticancer effects by modulating a diversity of signaling pathways, including nuclear factor-κB (NF-κB) and other pathways (15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the treatments of NPC are still problematic, and thus new therapeutic agents are required. Numerous studies have been tried to identify new naturally occurring chemopreventive or chemotherapy agents for using to inhibit cancer in vitro and in vivo (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%